2016
DOI: 10.1080/15384047.2016.1139236
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing detects structural variants in cancer

Abstract: Despite advances in sequencing, structural variants (SVs) remain difficult to reliably detect due to the short read length (<300 bp) of 2nd generation sequencing. Not only do the reads (or paired-end reads) need to straddle a breakpoint, but repetitive elements often lead to ambiguities in the alignment of short reads. We propose to use the long-reads (up to 20 kb) possible with 3rd generation sequencing, specifically nanopore sequencing on the MinION. Nanopore sequencing relies on a similar concept to a Coult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 23 publications
2
77
0
Order By: Relevance
“…The problem is acute in cancer, where examples of copy number variants, gene duplications, deletions, insertions, inversions, and translocations are common. For reads that averaged 8 kb in length, Norris et al [45] used the MinION to detect structural variants in a pancreatic cancer cell line. These authors concluded that the MinION allowed for reliable detection of structural variants with only a few hundred reads compared to the millions of reads typically required when using NGS platforms.…”
Section: Benefits Of Minion Compared To Other Next Generation Sequencmentioning
confidence: 99%
“…The problem is acute in cancer, where examples of copy number variants, gene duplications, deletions, insertions, inversions, and translocations are common. For reads that averaged 8 kb in length, Norris et al [45] used the MinION to detect structural variants in a pancreatic cancer cell line. These authors concluded that the MinION allowed for reliable detection of structural variants with only a few hundred reads compared to the millions of reads typically required when using NGS platforms.…”
Section: Benefits Of Minion Compared To Other Next Generation Sequencmentioning
confidence: 99%
“…ONT has released several versions of flowcells, where data quality and throughput vary significantly [18]. The release of version R7+ flowcells to the MAP community received positive feedback from different users who were using them for different applications.…”
Section: Data Formats and Base-callingmentioning
confidence: 99%
“…The release of version R7+ flowcells to the MAP community received positive feedback from different users who were using them for different applications. Norris et al [18] compared the data quality of different flowcell versions. Using R7 flowcells, the average base accuracy was only 67.4% for the reads produced, with 24.2% mismatched bases, 7.5% insertions, and 8.3% deletions.…”
Section: Data Formats and Base-callingmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies that have emerged earlier this decade provide linked-read sequencing, which uniquely barcodes individual long molecules prior to fragmentation and NGS (Zheng et al, 2016). Long-read sequencing (or third generation MPS) has already been used to sequence the human genome, and has demonstrated its potential to resolve complex structural rearrangements in patients with congenital chromothripsis and cancer, indicating its utility for use in clinical and diagnostic settings (Jain et al, 2018;Norris et al, 2016;Cretu Stancu et al, 2017;Pollard et al, 2018).…”
Section: Current Challenges With Mps "Read Lengths" and Defining Refementioning
confidence: 99%